Clinical and diagnostic features of dengue haemorrhagic fever in children - Reddy, Gomathi Chenna; K., Nagendra (International Journal of Contemporary Pediatrics, 2018)
Background: Diagnosis of dengue hemorrhagic fever (DHF) in children is based on clinical suspicion and prompting laboratory criteria. Methods: This prospective study in children (6 months-14 years) presenting with features of DHF aimed to identify symptoms and signs, laboratory parameters for in early detection and assessed the association between clinical, laboratory, immunological parameters and outcome. Results: Of 50 children, 26 were females, mean±SD age was 8.3±3.02 years; age group 8-12 years were affected the most (38.0%) and infants the least (4.0%). Fever (100%), followed by skin rash (56.0%), myalgia (52.0%) and head ache (48.0%) were the symptoms. Fever of 4-5 days (52.0%), high grade fever (84.0%) and of sudden onset (76.0%) were common. Ascitis was seen in nine. Peteche and malena (48.0%) were predominant manifestation of bleeding tendency (100%). Positive tourniquet test (48.0%) did not correlate with bleeding tendency. Lower levels of Hemoglobin (<12gms%, 100%), hematocrit (<40%, 98.0%), platelet count (<100000/mm3, 100%), serum albumin (76.0%), and abnormal liver enzymes (64.0%) along with prolonged prothrombin time (44.0%) and aPTT (18.05%) were noted. Ultrasound abdomen confirmed Pleural effusion (52.0%), ascitis (22.0%), Hepatomegaly (68.0%). Mean detection time was 4 days. Positive dengue IgM and IgG (60.0%), IgM (16%), and IgG (24%) were observed with increase of IgM in early phase. Conclusions: lower platelet count, raising haematocrit, increased liver enzymes with low serum albumin levels are early indicators. Prolonged PT and APTT are associated with severe bleeding manifestations. Apart from clinical expertise, chest X-ray, abdominal ultrasonogram are useful diagnostic tools.